1999
DOI: 10.1097/00001756-199906230-00035
|View full text |Cite
|
Sign up to set email alerts
|

Mouse epidermal growth factor-responsive neural precursor cells increase the survival and functional capacity of embryonic rat dopamine neurons in vitro

Abstract: We have grown expanded populations of epidermal growth factor (EGF)-responsive mouse striatal precursor cells and subsequently co-cultured these with primary E14 rat ventral mesencephalon. The aim of these experiments was to induce dopaminergic (DA) neuronal phenotypes from the murine precursors. While no precursor cell-derived neurons were induced to express tyrosine hydroxylase (TH), there was a dramatic 30-fold increase in the survival of rat-derived TH-positive neurons in the co-cultures. The effect was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…This finding, although surprising, is consistent with the observation that NSCs isolated from the neonatal mouse subventricular zone also secrete Sonic Hedgehog (Shh; Rafuse et al, 2005). These Shh-secreting NSCs support the survival of dopaminergic neurons when co-cultured with ventral midbrain tissue (Rafuse et al, 2005) and when transplanted into a mouse model of Parkinson's disease (Ostenfeld et al, 1999). Shh may also provide a survival advantage to NSCs over ESCs under serum-free, low density conditions.…”
Section: Hedgehog's Role In Proliferation Of Primitive Ectoderm-like supporting
confidence: 79%
“…This finding, although surprising, is consistent with the observation that NSCs isolated from the neonatal mouse subventricular zone also secrete Sonic Hedgehog (Shh; Rafuse et al, 2005). These Shh-secreting NSCs support the survival of dopaminergic neurons when co-cultured with ventral midbrain tissue (Rafuse et al, 2005) and when transplanted into a mouse model of Parkinson's disease (Ostenfeld et al, 1999). Shh may also provide a survival advantage to NSCs over ESCs under serum-free, low density conditions.…”
Section: Hedgehog's Role In Proliferation Of Primitive Ectoderm-like supporting
confidence: 79%
“…This suggests a protective effect from secreted factors produced by the hNPC (Po0.001; Figure 2a and c) and supports our earlier observations that neural stem cells alone can increase the survival of primary dopamine neurons. 35 Supernatant from hNPC-GDNF had effects on overall dopamine neuron number comparable to that produced from wild-type hNPC ( Figure 2c). In contrast, conditioned supernatant from hNPC-GDNF significantly increased both dopamine neuron neurite outgrowth and cell body area when compared with supernatant from wild-type hNPC (Po0.001; Figure 2b, d and e).…”
Section: Gdnf Release From Hnpc Is Physiologically Active In Vitromentioning
confidence: 76%
“…Administration of FGF‐8 and Shh together induces DA neuron differentiation in the dorsal diencephalon, suggesting that both are necessary and sufficient for early specification of DA neurons from progenitors in many regions anterior to the mid–hindbrain boundary (Ye et al ., 1998; Hynes & Rosenthal, 1999). However, it has been observed that administration of Shh and FGF‐8 to cell aggregates of human or rodent mesencephalic precursors has no effect on induction of DA phenotypes (Ostenfeld et al ., 1999; Svendsen et al ., 1999). This suggests that both of these molecules may be endogenously produced in the aggregates and therefore that their absence is not responsible for the poor spontaneous differentiation of DA neurons from mesencephalic precursors.…”
Section: Discussionmentioning
confidence: 99%